Relación de LYVE-1 con biomarcadores inflamatorios y regenerativos: análisis comparativo en individuos sanos y pacientes con pancreatitis crónica. - Guevara Tirado, Alberto (Medicina Interna de México, 2025)
OBJECTIVE: To analyze and compare the relationship between LYVE-1 and the inflammatory and regenerative biomarkers TFF-1, creatinine, REG-1A, REG-1B, and CA19-9 in healthy individuals and patients with chronic pancreatitis. MATERIALS AND METHODS: Analytical, cross-sectional study using secondary data from an open-access article reviewing the role of urinary biomarkers in the early detection of pancreatic cancer. Correlations between LYVE-1 and other biomarkers were analyzed using Spearman's correlation coefficient and multivariate linear regression models. The results were stratified by study group. RESULTS: A total of 119 healthy subjects and 183 patients with pancreatitis were analyzed. In the former, the correlations of LYVE-1 were: REG-1B (rho = 0.544; p < 0.001), REG-1A (rho = 0.553; p < 0.001), TFF-1 (rho = 0.464, p < 0.001), creatinine (rho = 0.282, p = 0.002), CA19-9 (rho = 0.343; p = 0.006). In patients with pancreatitis: TFF-1 (rho = 0.725; p < 0.001), creatinine (r = 0.659; p < 0.001), REG-1B (rho = 0.459; p < 0.001). REG-1A (rho = 0.492; p < 0.001) and plasma CA19-9 (rho = 0.410; p < 0.001). In chronic pancreatitis, the regression model showed that REG-1B (B = 0.012; p = 0.003) was the only factor associated with LYVE-1, with an R of 0.386. The model was statistically significant (F = 4.778; p = 0.002). CONCLUSIONS: LYVE-1 shows distinct patterns of association with biomarkers of regeneration, inflammation, and organ dysfunction in healthy individuals and patients with pancreatitis. Its dynamic role, adapted to homeostatic or inflammatory contexts, positions it as an integral biomarker for the assessment and monitoring of pancreatitis and its systemic complications.